Π–π stacking induced high current density and improved efficiency in ternary organic solar cells. Issue 21 (17th May 2018) - Li, Lijuan; Lin, Hui; Kong, Xiao; Du, Xiaoyang; Chen, Xinwei; Zhou, Ling; Tao, Silu; Zheng, Caijun; Zhang, Xiaohong
Abstract : We demonstrated that strengthening π–π stacking is an effective way to improve the efficiency of organic solar cells. Abstract : Ternary blend systems have been used to enhance the short-circuit current density ( J SC ) and fill factor (FF) of organic solar cells (OSCs). However, it is still a challenge to find suitable third components that concurrently possess complementary light absorption and well-matched energy levels. Here, a small organic molecule, 4, 4′-(9, 9-dihexyl-9 H -fluorene-2, 7-diyl)bis( N, N -bis(4-(pyren-1-yl)phenyl)anili-ne) (DFNPy), which contains a triphenylamine core and bulky pyrene rings, was designed and used to construct ternary blend OSCs. DFNPy shows complementary absorption spectra in the 350–450 nm shortwave band, which has seldom been reported in the field of ternary OSCs. Furthermore, the bulky pyrene rings aggregate via π–π stacking to promote charge transfer. As a result, a high power conversion efficiency (PCE) of 10.59% with an enhanced J SC of 19.72 mA cm −2 was realized in PTB7-Th:DFNPy:PC71 BM-based ternary OSCs. The addition of DFNPy was found to modulate the film morphology by improving the film phase separation and crystallinity, which can facilitate charge generation and decrease charge recombination, resulting in enhanced mobility. The results demonstrate an effective strategy for improving the photovoltaic performance of OSCs.